2008
DOI: 10.1115/1.2960492
|View full text |Cite
|
Sign up to set email alerts
|

Soret Effect for a Ternary Mixture in Porous Cavity: Modeling With Variable Diffusion Coefficients and Viscosity

Abstract: A porous cavity filled with methane (C1), n-butane (nC4), and dodecane (C12) at a pressure of 35.0MPa is used to investigate numerically the flow interaction due to the presence of thermodiffusion and buoyancy forces. A lateral heating condition is applied with the left wall maintained at 10°C and the right wall at 50°C. The molecular diffusion and thermal diffusion coefficients are functions of temperature, concentration, and viscosity of mixture components. It has been found that for permeability below 200md… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… The Soret effect of two ternary mixtures in a homogenous porous medium cavity was studied for different permeabilities. A publication related to this contribution is Jaber and Saghir ( 2006), Jaber et al (2008a), andJaber et al (2008b).…”
Section:   mentioning
confidence: 99%
“… The Soret effect of two ternary mixtures in a homogenous porous medium cavity was studied for different permeabilities. A publication related to this contribution is Jaber and Saghir ( 2006), Jaber et al (2008a), andJaber et al (2008b).…”
Section:   mentioning
confidence: 99%
“…Initially, the Dougherty and Drickamer model was modified for predicting thermodiffusion coefficients for binary linear chain hydrocarbon mixtures [19]. Thermodiffusion coefficients of C 10 À nC i (i ¼ 5, 6,7,15,16,17,18), C 12 À nC i (i ¼ 5, 6,7,8,9), and C 18 À nC i (i ¼ 5, 6,7,8,9,12) were calculated by the new proposed model. Comparisons of the calculated theoretical results with the experimental data showed a good performance of the proposed model.…”
Section: Molecular Diffusion and Thermodiffusion Modelmentioning
confidence: 99%
“…Results showed that the natural convection has an important role on the phase distribution in the gas and oil non-isothermal medium. Jaber et al [8] simulated Soret effect for a ternary mixture in porous cavity considering variable viscosity and diffusion coefficients. It was found that for a permeability below 200 md, the thermodiffusion has a dominant effect; and above this level, buoyancy convection becomes the dominant mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the separation ratio, characterizing the Soret effect and the normalized porosity are investigated theoretically and numerically. Many investigations devoted to study the Soret effect on the onset of convection in binary and ternary mixtures in a porous medium can be found in the articles by Goldobin and Lyubimov (2007); Mansour et al (2007Mansour et al ( , 2008 ;Jaber et al (2008); Narayana et al (2008); Gaikwad et al (2009a,b). Recently, the effects of Brownian diffusion and the thermophoresis were applied to the HortonRogers-Lapwood problem (the onset of convection in a horizontal layer of a porous medium uniformly heated from below) by Nield and Kuznetsov (2009) and Nield (2010, 2011).…”
Section: Introductionmentioning
confidence: 98%